2017
DOI: 10.1155/2017/8402035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sp1 as a Transcription Activator to Regulate Fibroblast Growth Factor 21 Gene Expression

Abstract: Fibroblast growth factor 21 (FGF21) is a metabolic hormone with multiple beneficial effects on lipid and glucose homeostasis. Previous study demonstrated that FGF21 might be one of the Sp1 target genes. However, the transcriptional role of Sp1 on FGF21 in adipose tissue and liver has not been reported. In this study, we found that the proximal promoter of mouse FGF21 is located between −63 and −20 containing two putative Sp1-binding sites. Sp1 is a mammalian transcription factor involved in the regulation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Since the identification of FGF21 as a new member of the FGF family back in 2000 [51], the FGF21 promoter has been exhaustively characterized. Besides the description of the PPARa binding site (PPRE) present in FGF21 regulatory sequences [14], several other transcription factors have been identified to bind to particular promoter sequences and to induce transcriptional activity, such as activating transcription factor 2 (ATF2) [52], ATF4 [53], Sp1 [54], among several others [55]. Contradictory results on Bmal1/Clockmediated activation of the Fgf21 promoter have been previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…Since the identification of FGF21 as a new member of the FGF family back in 2000 [51], the FGF21 promoter has been exhaustively characterized. Besides the description of the PPARa binding site (PPRE) present in FGF21 regulatory sequences [14], several other transcription factors have been identified to bind to particular promoter sequences and to induce transcriptional activity, such as activating transcription factor 2 (ATF2) [52], ATF4 [53], Sp1 [54], among several others [55]. Contradictory results on Bmal1/Clockmediated activation of the Fgf21 promoter have been previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…The regulation of SP1 with regards to target genes is achieved by binding of the DNA binding domain to GC-rich motifs in the promoter region of the target gene, thereby regulating cellular processes such as autophagy, apoptosis, proliferation, differentiation and angiogenesis ( 36 , 37 ). Chen et al ( 38 ) found that Sp1 binding sites in the core promoter region are essential for positive regulation of FGF21 ( Fibroblast growth factor 21 ) through gene transcription in both hepatic and adipose tissue ( 38 ). Furthermore, a recent study found that an SNP g.133A>C located within the SCD ( Stearoyl CoA desaturase ) promoter generated overall higher Sp1 binding affinity to the SCD promoter, which consequently affected gene expression ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the regulator involved in Fgf21 induction might be modulated differently in different tissues. Indeed, Sp1, a mammalian transcriptional factor, binds to the Fgf21 promoter and increases the expression of Fgf21 [ 58 ]. Interestingly, Sp1 protein expression in mice with diet-induced obesity was much higher in white adipose tissue than in the liver.…”
Section: Discussionmentioning
confidence: 99%